Emprendimiento y crecimiento económico en America Latina 2009 – 2018 - Gabriela Stefanía, Baldeón Muñoz (2021)
economic growth in ten Latin American countries is analyzed, during the period 2009-2018. The main objective is to know the effect between these two variables, considering innovation and investment in the region as control variables, for this the theory of the innovative entrepreneur is exposed in which it relates entrepreneurial activity and economic growth since decisions investment and production favor the creation of wealth and promote economic growth, a Varma estimation with panel data is applied. The results indicate that for each increase in the entrepreneurship rate the PIB per capita will increase by 6%, it is verified that there is a positive and significant relationship between the level of entrepreneurship and the economic growth of the ten countries studied. Key Words: Entrepreneurship, economic growth. Reviewed by: Mgs. Sonia Granizo Lara ENGLISH PROFESSOR. C.c. 0602088890